Radial strichartz estimates with application to the 2-D Dirac-Klein-Gordon system - Ovcharov, Evgeni Y. (Communications in partial differential equations, 2012)
We prove Strichartz estimates for data with spherical symmetry for a large class of dispersive equations. Our method is based on weighted space-time estimates and does not rely on the dispersive estimate. The dual inhomogeneous Strichartz estimates are derived too and it is shown that in the context of the wave and the Klein-Gordon equation the results that we obtain are essentially optimal. Furthermore, we extend the inhomogeneous estimates to the range . We also give an application to the global well-posedness of the Dirac-Klein-Gordon system in two spatial dimensions. For data that is spherically symmetric we improve the regularity assumptions of the recent result of Grünrock and Pecher [13].